Experimental Validation of a Three-Phase Off-Board Electric Vehicle Charger With New Power Grid Voltage Control - Yong, Jia Ying; Ramachandaramurthy, Vigna K.; Tan, Kang Miao; Selvaraj, Jeyraj (Institute of Electrical and Electronics Engineers, 2018)
The deployment of electric vehicles (EVs) protects the environment by reducing carbon emissions. Since plugged-in EVs require energy from the power grid to charge their batteries, the charger component is inevitable. With the appropriate control, additional functions can be achieved with the existing charger's converter topology. This paper discussed the implementation of a new control strategy in a three-phase off-board EV charger, which provided grid voltage regulation while charging the vehicle. The vehicle charging control (P-control) and grid voltage regulation control (V-control) were implemented in the back-end DC/DC converter and front-end AC/DC converter of the charger, respectively. The proposed P-control utilized the constant current/reduced constant current charging approach to rapidly charge the battery while alleviating battery deterioration. Meanwhile, the proposed V-control had the capability to regulate the grid voltage and DC-link voltage during the EV charging process. Besides the PSCAD/EMTDC simulation, experimental testing was performed on a 2 kVA laboratory EV charger to validate the control performance. While complying with the harmonic standards, the experimental results showed that the charger prototype effectively regulated the grid voltage to the pre-charge voltage while maintaining the DC-link voltage at 150 V during various charging currents of up to 5 A.